Pengaruh Perceived Benefit, Percieved Risk, Ewom, Trust, Online Purchase Intention, Actual Purchase pada Perilaku Konsumen Terhadap Pembelian Bodycare di Marketplace - Fitri Nurhazizah (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
Sophisticated technological devices have provided an important role in marketing strategies that can be used by companies to make it easier for consumers to carry out online shopping activities. The purpose of this study is to address the direct or indirect influence on purchase intention to actual purchase. This research was conducted to examine the effect of Perceived Benefit, Online Purchase Intention, Actual Purchase, EWOM and Trust on consumer behavior towards purchasing Bodycare in the Marketplace. Primary data in this study were collected through a questionnaire with a total of 164 respondents who live in Jabodetabek and have purchased Bodycare at Maketplace and have shopped once in three months. The data analysis technique used by researchers in this study is the partial least squares structural equation model. The results of this study indicate that four of the eight proposed hypotheses are accepted, while the rest are rejected. The contribution of this research is expected to be able to add information about the theoretical/scientific level of marketing management.